Fast front kick: gaining insights beyond the data - Landeo, R.; McIntosh, A. S. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The purpose of this study was to examine sets of kinematic variables obtained from Taekwondo fast front kick and to asses their potential use for movement analysis. Kinematic data were divided into three categories; i) Peak velocities (PV), ii) Normalised time to reach peak velocities (TPV) and iii) Intersegmental timing and calculated performance variables (TCV). Expert and novice participants (n=40) performed a set of three fast front kicks and squat and counter movement jumps. No correlation between TPV variables and skill (< 0.25) or execution speed (< 0.2) was found, while group mean differences are not significant (p > 0.52). Skill is better assessed from TCV (group mean differences p< 0.0001). A stronger correlation between peak velocities and jumping ability (0.84) than to skill (0.51) was found.